Distinction between inflection and derivation of learning reduplication in Mandarin - Shi Yuxin; I Dewa Putu Wijana; Y. Tri Mastoyo; Hermina Sutami (Intelektual Pustaka Media Utama, 2019)
Reduplication as a word-formation process in Mandarin, which is one of the most difficult knowledge to comprehend for scholar and student. Theoretically this research offers an approach that is different from what has been made by previous researchers. Using the M.D.S Simatupang free context approach this research contrasts the reduplicative forms of all word classes and shows the relationships between them (AA, AABB, ABAB, ABB) and their basic forms (A, AB), then based on test of categorical word and test of lexical decomposition as proposed by J.W.M Verhaar, this study analyzes and explains reduplication and inflectional reduplication in Mandarin in order to students understand as their meaning vocabularies. As a result, this research examines the derivational and inflectional reduplication in Mandarin all at once can disseminate the use of morphological theory. In addition, this study discusses Mandarin reduplication based on various word classes that are contained as a basis for the relevant form of reduplication. Beginner research results will be presented in this study in order to stimulate more complete writing, it will be better if this research can be disseminated in order to add learning and reading material for future research.